Lipases imobilizadas em suportes híbridos como biocatalisadores para a produção de ésteres de açúcares - Vescovi, Vinicius (2016)
The use of lipases in large scale processes is limited due to their high cost. The reuse of the catalyst can contribute to make the enzymatic process more attractive. Hydrophobic supports are the mostly used for lipase immobilization, due to the mechanism of interfacial activation in the presence of hydrophobic interface. However, enzyme physically adsorbed to the support does not allow high operational stability. Therefore, in this work was evaluated the immobilization of commercial lipases from Candida antarctica type B (CALB), Thermomyces lanuginosus (LTL) e Pseudomonas fluorescens (LPF) on hybrid supports, that enable the hydrophobic adsorption, followed by covalent linkage between the adsorbed enzyme and the activated support. Silica was activated with trietoxy(octyl)silane (OCTES), (3-aminopropyl)trietoxysilane (APTES) e 3-glycidyloxypropyl)trimetoxysilane (GPTMS), aiming to produce supports with different functionality, as following: silica containing octyl groups (octyl-silica, OS), octyl and aldehyde groups (octyl-silica-glyoxyl and octyl-silicaaldehyde, OSGlx and OSGlu, respectively), and silica containing octyl and epoxy groups (octyl-silica-epoxy, OSEpx). From adsorption assays using the hydrophobic dye Rose of Bengal it was found that the modification of the silica with OCTES significantly increased the hydrophobicity of all the supports. Silica modified with OCTES groups showed to be 4 times more hydrophobic than non-modified silica. The support OSGlu yielded more active CALB biocatalyst, while OS yielded more active biocatalysts prepared with PFL and TLL. All the biocatalysts showed high stability in tert-butanol, specially CALB immobilized on OSGlu (OSGlu-CALB), maintaining 95% of its initial activity after 168 h at 60 ºC. CALB-OSGlu was successfully used in the synthesis of fructose oleate at 55ºC, yielding up to 70% conversion after 9 cycles of 6 hours, while the commercial biocatalyst Novozyme 435 retained around 53%. TLL and PFL were used in the synthesis of fructose oleate at 35ºC in presence of different amounts of water. All biocatalysts showed excellent performance in the ester synthesis when small amount of water (1%, v/v) was added to the organic phase, except for the lipases immobilized on silica modified with octyl and epoxy groups (OSEpx). Small amount of water increased around 5-times the ester productivity compared to reaction without water. Conversions around 70% were achieved at low temperature (35ºC) and short time of reaction (30 min). These results represent an advance in this field from of industrial point of view, where productivity is a relevant parameter for large-scale processes. Finally, porcine pancreatic lipase (PPL) immobilized on OS was used in the synthesis of xylose oleate and xylose caprilate, because it is the most inexpensive lipase commercially available. The results showed to be promising, because conversions around of 70% were achieved after 2 h of reaction at 60 oC. Generally, this work showed that the chemical modification of the silica surface with different active groups allowed the preparation of biocatalysts with different microenvironment, which exhibits an important role in the activity and stability of the immobilized enzymes. Besides, the biocatalysts prepared in this work showed excellent performance and operational stability in syntheses of sugar esters, showing to have potential for industrial application.